The impact of Baduanjin as a form of exercise snack on the physical and mental health of sedentary college students - Xiaobin Wang; Witid Mitranun (Retos, 2026)
Background: Exercise snacks are a time-efficient strategy to mitigate the adverse effects of sedentary behavior. However, evidence regarding the use of Baduanjin as exercise snacks remains limited. Objective: This study aimed to evaluate the long-term effects of a Baduanjin-based exercise snacks intervention on body composition, physical fitness, and mental health in college students, and to examine differences across body mass index (BMI) subgroups of normal-weight and overweight. Methods: Sixty sedentary college students were stratified and randomly assigned to either an experimental or control group: experimental-normal BMI (EG-NB, n = 15), experimental-overweight/obese (EG-OB, n = 15), control-normal BMI (SCG-NB, n = 15), and control-overweight/obese (SCG-OB, n = 15). The experimental groups participated in a 12-week Baduanjin exercise snack intervention consisting of three daily sessions (8 min/session), five days per week, whereas the control groups maintained their usual lifestyle and physical activity levels. A mixed-design ANOVA examined group × time interactions. Results: After the 12-week intervention, significant time × group interactions were observed for body weight, BMI, muscle mass, vertical jump performance, and self-esteem (all p < 0.05). The EG-OB group showed significant reductions in body weight and BMI compared with baseline (p < 0.05). Vertical jump performance significantly declined in both control groups, whereas no significant reductions were observed in the experimental groups. In addition, Rosenberg Self-Esteem Scale scores significantly increased in both experimental groups (both p < 0.05). Conclusion: Baduanjin-based exercise snacks may improve body weight, BMI, and self-esteem while maintaining lower-body explosive performance, particularly in overweight individuals.